HASIL JADI PENERAPAN “TEKNIK SPONGING” DALAM MATA PELAJARAN PILIHAN MELUKIS PADA TOTE BAG DENGAN MEDIA VIDIO PEMBELAJARAN DI SMK NEGRI 3 KEDIRI - Mu’iz Afifah; Yunus Karyanto (Cendikia: Jurnal Pendidikan dan Pengajaran, 2025)
The research method used is descriptive qualitative with a case study approach. The subjects of the study were 11th-grade students enrolled in the elective painting course. Data were collected through observation, interviews, documentation, and questionnaires. Instructional videos were used as the primary media to deliver the sponging technique material, enabling students to understand and apply it more easily and independently. The results showed that the application of the sponging technique, supported by video-based learning media, effectively enhanced students’ painting skills on tote bags. Students became more enthusiastic, creative, and meticulous in creating artworks. The instructional videos also proved effective in visualizing the steps of the sponging technique systematically, making the learning process more engaging and meaningful.